Easy fabrication of high quality nickel mold for deep polymer microfluidic channels. (9th May 2016) - Wong, Ten It; Limantoro, Julian; Fong, Kin Phang; Tan, Christina Yuan Ling; Quan, Chenggen; Sun, Ling Ling; Zhou, Xiaodong
Abstract: Mass fabrication of disposable microfluidic chips with hot embossing is a key technology for microfluidic chip based biosensors. In this work, we develop a new method of fabricating high quality and highly durable nickel molds for hot embossing polymer chips. The process involves the addition of a thick, patterned layer of negative photoresist AZ-125nxT to a 4″ silicon wafer, followed by nickel electroplating and delamination of the nickel mold. Our investigations found that compared to a pillar mask, a hole mask can minimize the diffraction effect in photolithography of a thick photoresist, reduce the adhesion of the AZ-125nxT to the photomask in photolithography, and facilitate clean development of the photoresist patterns. By optimizing the hot embossing and chip bonding parameters, microfluidic chips with deep channels are achieved.